2022
DOI: 10.1002/slct.202104213
|View full text |Cite
|
Sign up to set email alerts
|

Photostability and Halochromic Properties of Near‐Infrared Absorbing Anionic Heptamethine Cyanine Dyes

Abstract: We synthesized near-infrared-absorbing anionic heptamethine cyanine (HMC) dyes and investigated their photostability and halochromic properties in detail. Upon changing the methyl groups of the anionic HMC dye to phenyl or perfluorophenyl groups, the maximum absorption wavelengths of the dye solutions were red-shifted and dye photostability in solution under white LED irradiation at 25 °C was improved. The anionic HMC dye featuring methyl groups presented halochromic properties in solution, and the solution co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The HRMS data revealed that the photodegradation of SQ dye 2 b occurred via the electrophilic addition of singlet oxygen to the alkene moieties of dye 2 b, similar to the photo-decomposition of hepthamethine cyanine dyes. [8,9] Based on the results of the photodegradation experiments in CH 2 Cl 2 , the high photostability of ring-perfluorinated SQ dye 2 a can be explained as follows. The introduction of electronwithdrawing fluorine atoms into the benzoindolenine ring reduced the electron density of the alkene moiety of SQ dye 2 a and prevented the electrophilic addition of singlet oxygen.…”
Section: Chemistryselectmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRMS data revealed that the photodegradation of SQ dye 2 b occurred via the electrophilic addition of singlet oxygen to the alkene moieties of dye 2 b, similar to the photo-decomposition of hepthamethine cyanine dyes. [8,9] Based on the results of the photodegradation experiments in CH 2 Cl 2 , the high photostability of ring-perfluorinated SQ dye 2 a can be explained as follows. The introduction of electronwithdrawing fluorine atoms into the benzoindolenine ring reduced the electron density of the alkene moiety of SQ dye 2 a and prevented the electrophilic addition of singlet oxygen.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Previously, we investigated the photodegradation of anionic heptamethine cyanine dyes with low photostability in solution and found that the introduction of fluorine atoms and fluorine-containing substituents into the dyes significantly improved their photostability and thermostability. [8,9] However, no detailed mechanism for the photodegradation of SQ dyes has been elucidated. Herein, we report the synthesis, photophysical properties, and photodegradation details of benzoindolenine-based SQ dyes in solution and poly(methyl methacrylate) (PMMA) films.…”
Section: Introductionmentioning
confidence: 99%
“…As we continue our research into the synthesis, properties, and utilization of a wide variety of HMCDs, 8 we report herein the preparation of an organic–inorganic hybrid material comprising indolenine-based HMCD adsorbed on silica gel and the first demonstration of its vapochromism to amines and chlorinated solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, anionic HMC dyes exhibit superior optical properties, including a red-shifted maximum absorption wavelength (λ max ) relative to their cationic counterparts. However, comparatively lower photostability hinders their application [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that introducing perfluorophenyl groups into an anionic HMC dye resulted in more red-shifted λ max and higher photostability of the dye than those with methyl or phenyl groups [ 37 ]. Since the mechanism of photolysis of HMC dyes is based on the addition of an electrophilic singlet oxygen to a double bond, the introduction of electron-withdrawing properties into the HMC dye backbone should be the most powerful means of improving its photostability.…”
Section: Introductionmentioning
confidence: 99%